The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2013
DOI: 10.1109/ceidp.2013.6748164
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of TiO<inf>2</inf> and ZnO nanoparticle concentration on electrical insulation characteristics of insulating oil

Abstract: This paper presents that mineral oil and linear alkylbenzene with dispersed metal oxide nanoparticles were investigated to clarify the effect of nanoparticles on AC breakdown strength and relative permittivity characteristics. The materials of nanoparticles were selected at TiO 2 (crystal structure of anatase and rutile) and ZnO. The nanoparticle concentrations of samples were prepared varying from 0 to 0.5 vol% into mineral oil or linear alkylbenzene by ultrasonic dispersion. AC (60 Hz) breakdown test was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…These authors concluded that the addition of different TiO2 concentrations produced different increases in the breakdown strength of nanofluid samples. Similar results with TiO2 nanoparticles were obtained by Yue-fan et al [10,11] and Hanai et al [12]. Other papers have evaluated if the positive effect of nanoparticles on dielectric properties of mineral oil is kept with accelerated thermal aging.…”
Section: Introductionsupporting
confidence: 84%
“…These authors concluded that the addition of different TiO2 concentrations produced different increases in the breakdown strength of nanofluid samples. Similar results with TiO2 nanoparticles were obtained by Yue-fan et al [10,11] and Hanai et al [12]. Other papers have evaluated if the positive effect of nanoparticles on dielectric properties of mineral oil is kept with accelerated thermal aging.…”
Section: Introductionsupporting
confidence: 84%
“…In the following section the positive impulse breakdown voltage with respect to concentration and type of nanoparticles are presented. A lot of research has been carried out to measure the impulse breakdown strength of mineral oil-based and vegetable oil-based nanofluids [22,23,27,31,37,61,72]. Figure 10.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Aiming at improvement of electrical insulation properties of insulating oil, various researches were conducted in the recent years on insulating oil with dispersed nanoparticles; due to addition of nanoparticles, a number of improvements in oil characteristics were confirmed, such as heat conductivity, permittivity, and AC breakdown voltage (BDV) [2][3][4][5]. However, much remains unknown about behavior of nanoparticles in insulating oil and breakdown mechanisms.…”
Section: Introductionmentioning
confidence: 99%